AN AUTOMATED FLEXIBLE FIXTURE SYSTEM FOR MASS CUSTOMIZATION - Illidge, Andrew; Bright, Glen (The South African Journal of Industrial Engineering, 2018)
The need for mass customisation is growing as customer demand for customised products increases. Mass customisation is the production of custom products at mass-produced rates. Current fixture technology does not possess the flexibility required for mass customisation. It was determined, through research, that if mass customisation is to be achieved, a fixture system is required that possesses the following attributes: it accommodates a large variety of part families and geometries; it has automated setups and setup changeovers; it has a semi-automated fixture design; and it provides adaptive feedback during machining processes. A fixture system, known as an automated flexible fixture system (AFFS), was developed that met these requirements. The AFFS was researched, designed, manufactured, and tested. The tests involved determining the AFFS’s response to changes in cutting conditions. The AFFS’s response to the tests indicated that it behaved normally, for the most part, with higher feed rates and spindle speeds generally yielding higher or more vibrational frequency bands. Further development is required before the AFFS meets commercial standards. However, as a proof of concept it was successful. This paper presents the developed AFFS in more detail.